Goldilocks Days: optimising children's time use for health and well-being. Issue 3 (12th August 2021) - Dumuid, Dorothea; Olds, Timothy; Lange, Katherine; Edwards, Ben; Lycett, Kate; Burgner, David P; Simm, Peter; Dwyer, Terence; Le, Ha; Wake, Melissa
Abstract : Background: One size rarely fits all in population health. Differing outcomes may compete for best allocations of time. Among children aged 11–12 years, we aimed to (1) describe optimal 24-hour time use for diverse physical, cognitive/academic and well-being outcomes, (2) pinpoint the 'Goldilocks Day' that optimises all outcomes and (3) develop a tool to customise time-use recommendations. Methods: In 2004, the Longitudinal Study of Australian Children recruited a nationally-representative cohort of 5107 infants with biennial follow-up waves. We used data from the cross-sectional Child Health CheckPoint module (2015–2016, n=1874, 11–12 years, 51% males). Time use was from 7-day 24-hour accelerometry. Outcomes included life satisfaction, psychosocial health, depressive symptoms, emotional problems, non-verbal IQ; vocabulary, academic performance, adiposity, fitness, blood pressure, inflammatory biomarkers, bone strength. Relationships between time use and outcomes were modelled using compositional regression. Results: Optimal daily durations varied widely for different health outcomes (sleep: 8.3–11.4 hours; sedentary: 7.3–12.2 hours; light physical activity: 1.7–5.1 hours; moderate-to-vigorous physical activity (MVPA): 0.3–2.7 hours, all models p≤0.04). In general, days with highest physical activity (predominantly MVPA) and low sedentary time were optimal for physical health, while days with highest sleep and lowest sedentary time were optimal for mental health. Days with highest sedentary time and lowest physical activity were optimal for cognitive health. The overall Goldilocks Day had 10 hours 21 min sleep, 9 hours 44 min sedentary time, 2 hours 26 min light physical activity and 1 hour 29 min MVPA. Our interactive interface allows personalisation of Goldilocks Days to an individual's outcome priorities. Conclusion: 'Goldilocks Days' necessitate compromises based on hierarchies of priorities for health, social and economic outcomes.